Design and Analysis of Solar Refrigeration System Impaired by Chloro-Fluoro Refrigerants - Rejus Kumar, Arun V; Francis Britto, A. Sagai; Saravanan, N. (International Journal of Psychosocial Rehabilitation, 2019)
Solar energy is a periodic unsteady heat source. In the utilization of solar energy, direct recovery at about 100 °C is feasible and economical. In the solar-driven ejector-absorption refrigeration cycle with reabsorption of the strong solution and pressure boost of the weak solution. High COP is obtained by increasing the efficiency of the absorber with the help of ejectors (liquid-gas). Low-pressure refrigerant vapour is injected and pressurized into a high-pressure solution. Flow resistance is minimized. A small solution pump is used; in this system, there are no moving parts, no lubrication, low maintenance, and simple operation. Working fluids are based on salt absorbent, low evaporation temperature, and reducing the problem of crystallization. Working pairs used in the system is NH3 - H20 (or) NH3 - Lithium Nitrate